A WAKE UP CALL: RISING INCIDENCES OF ANXIETY DISORDER IN PAEDIATRIC POPULATION - DR. DEEPMALA U. YADAV; PROF. ABHIMANYU KUMAR (International Journal of Pharma and Bio Sciences, 2013)
Globally research literature on the epidemiology of childhood anxiety disorders is limited. As, many a-times anxiety disorder may not present clear cut disease like entities and may keep changing over time. Despite with these issues, incidence studies provide the possibility of assessing risk factors and help in conceptualising the progression of diseases and also guide for future endeavours of early manifestations, primary prevention, and comprehensive intervention. Present incidence study was conducted by survey method which was designed to check the incidence and severity of anxiety disorder in Indian childhood and adolescent population. For this, Devereux Scales of Mental Disorders (DSMD) was adopted for survey and as diagnostic and assessment criteria. Survey data was collected by simple random sampling method. The results were indeed a wake-up call for paediatricians, parents, school authorities and policy makers of public health services.